Pregunta
upstudy study bank question image url

19. \( \int_{3}^{3}\left(x^{2}+2 x-4\right) d x=\left[\frac{1}{3} x^{3}+x^{2}-4 x\right]_{1}^{3}=(9+9-12)-\left(\frac{1}{3}+1-4\right)=6+\frac{4}{3}=\frac{29}{3} \) 21. \( \int_{0}^{2}\left(\frac{4}{5} t^{3}-\frac{4}{4} t^{2}+\frac{2}{5} t\right) d t=\left[\frac{1}{3} t^{4}-\frac{1}{4} t^{3}+\frac{4}{8} t^{2}\right]_{0}^{2}=\left(\frac{4}{5}-2+\frac{4}{5}\right)-0=2 \) 23. \( \int_{1}^{3} \sqrt{x} d x=\int_{1}^{9} x^{1 / 2} d x=\left[\frac{x^{3 / 2}}{3 / 2}\right]_{1}^{3}=\frac{4}{4}\left[x^{3 / 2}\right]_{1}^{0}=\frac{4}{4}\left(9^{3 / 2}-1^{3 / 2}\right)=\frac{3}{3}(27-1)=\frac{24}{3} \) 25. \( \int_{\pi / 6}^{\pi} \sin \theta d \theta=[-\cos \theta]_{\pi / 6}^{\pi}=-\cos \pi-\left(-\cos \frac{\pi}{6}\right)=-(-1)-(-\sqrt{3} / 2)=1+\sqrt{3} / 2 \) 27. \( \int_{0}^{1}(u+2)(u-3) d u=\int_{0}^{1}\left(u^{2}-u-6\right) d u=\left[\frac{1}{3} u^{3}-\frac{1}{2} u^{2}-6 u\right]_{0}^{1}=\left(\frac{1}{3}-\frac{1}{2}-6\right)-0=-\frac{37}{6} \)

Ask by Zimmerman Vargas. in Yemen
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The integrals evaluate to the following: - **Problem 19**: \(0\) - **Problem 21**: \(\frac{46}{15}\) - **Problem 23**: \(2\sqrt{3} - \frac{2}{3}\) - **Problem 25**: \(1 + \frac{\sqrt{3}}{2}\) - **Problem 27**: \(-\frac{37}{6}\)

Solución

Let's go through each integral step by step, correcting any mistakes and ensuring clarity in the calculations. ### Problem 19 Evaluate the integral: \[ \int_{3}^{3}\left(x^{2}+2 x-4\right) d x \] 1. **Evaluate the definite integral**: Since the limits of integration are the same (from 3 to 3), the value of the integral is: \[ \int_{3}^{3} f(x) \, dx = 0 \] ### Problem 21 Evaluate the integral: \[ \int_{0}^{2}\left(\frac{4}{5} t^{3}-\frac{4}{4} t^{2}+\frac{2}{5} t\right) d t \] 1. **Find the antiderivative**: \[ F(t) = \left[\frac{1}{3} \cdot \frac{4}{5} t^{4} - \frac{1}{4} t^{3} + \frac{2}{5} \cdot \frac{1}{2} t^{2}\right] = \left[\frac{4}{15} t^{4} - \frac{1}{4} t^{3} + \frac{1}{5} t^{2}\right] \] 2. **Evaluate from 0 to 2**: \[ F(2) = \frac{4}{15} \cdot 16 - \frac{1}{4} \cdot 8 + \frac{1}{5} \cdot 4 = \frac{64}{15} - 2 + \frac{4}{5} \] Convert \(2\) to a fraction with a common denominator: \[ 2 = \frac{30}{15}, \quad \frac{4}{5} = \frac{12}{15} \] Thus, \[ F(2) = \frac{64}{15} - \frac{30}{15} + \frac{12}{15} = \frac{46}{15} \] And \(F(0) = 0\). 3. **Final result**: \[ \int_{0}^{2} \left(\frac{4}{5} t^{3}-t^{2}+\frac{2}{5} t\right) dt = \frac{46}{15} \] ### Problem 23 Evaluate the integral: \[ \int_{1}^{3} \sqrt{x} \, dx \] 1. **Find the antiderivative**: \[ F(x) = \left[\frac{2}{3} x^{3/2}\right] \] 2. **Evaluate from 1 to 3**: \[ F(3) = \frac{2}{3} \cdot 3^{3/2} = \frac{2}{3} \cdot 3\sqrt{3} = 2\sqrt{3} \] \[ F(1) = \frac{2}{3} \cdot 1^{3/2} = \frac{2}{3} \] 3. **Final result**: \[ \int_{1}^{3} \sqrt{x} \, dx = 2\sqrt{3} - \frac{2}{3} \] ### Problem 25 Evaluate the integral: \[ \int_{\pi / 6}^{\pi} \sin \theta \, d \theta \] 1. **Find the antiderivative**: \[ F(\theta) = -\cos \theta \] 2. **Evaluate from \(\frac{\pi}{6}\) to \(\pi\)**: \[ F(\pi) = -\cos(\pi) = 1 \] \[ F\left(\frac{\pi}{6}\right) = -\cos\left(\frac{\pi}{6}\right) = -\frac{\sqrt{3}}{2} \] 3. **Final result**: \[ \int_{\pi / 6}^{\pi} \sin \theta \, d \theta = 1 - \left(-\frac{\sqrt{3}}{2}\right) = 1 + \frac{\sqrt{3}}{2} \] ### Problem 27 Evaluate the integral: \[ \int_{0}^{1}(u+2)(u-3) \, du \] 1. **Expand the integrand**: \[ (u+2)(u-3) = u^2 - 3u + 2u - 6 = u^2 - u - 6 \] 2. **Find the antiderivative**: \[ F(u) = \left[\frac{1}{3} u^{3} - \frac{1}{2} u^{2} - 6u\right] \] 3. **Evaluate from 0 to 1**: \[ F(1) = \frac{1}{3} - \frac{1}{2} - 6 = \frac{1}{3} - \frac{3}{6} - \frac{36}{6} = \frac{1}{3} - \frac{39}{6} \] Convert \(\frac{1}{3}\) to sixths: \[ \frac{1}{3} = \frac{2}{6} \] Thus, \[ F(1) = \frac{2}{6} - \frac{39}{6} = -\frac{37}{6} \] 4. **Final result**: \[ \int_{0}^{1}(u+2)(u-3) \, du = -\frac{37}{6} \] ### Summary of Results - Problem 19: \(0\) - Problem 21: \(\frac{46}{15}\) - Problem 23: \(2\sqrt{3} - \frac{2}{3}\) - Problem 25: \(1 + \frac{\sqrt{3}}{2}\) - Problem 27: \(-\frac{37}{6}\)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

Have you ever thought about how integrals can represent areas? When you compute definite integrals, you’re really finding the area under a curve between two points on the x-axis! For example, the integral of \( x^2 + 2x - 4 \) from 3 to 3 is zero—because there’s no area when the limits are the same. In the realm of physics, integrals are everywhere! They're used to calculate quantities like distance, volume, and even work done. For instance, using integrals, you can find the work done by a variable force or determine the area under velocity-time graphs, showcasing how integral calculus isn't just academic, but a vital tool in understanding the real world.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad